1993
DOI: 10.1111/j.1467-1770.1993.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Readers' Memory for Narrative Texts: Evidence for Structure‐Preserving Top‐Down Processing

Abstract: This study assessed the role that structural properties of texts play in the mental representations of second-language (L2) readers. In particular, we investigated the extent to which 47 L2 readers of English used structural properties of a text (causal factors, story-grammar category, and hierarchical level) to "fill in" gaps in their mental representations. L2 readers' recall protocols of narrative texts were analyzed and compared with those of 72 L1 readers of English using two scoring criteria: meaning-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Our results are in accordance with those of Horiba et al (1993), who also observed more top-down processing in L2 English based on a sample of 17-and 18-year-old students. Their readers used more intrusions in L2, thus showing top-down elaborative processing that L2 readers use to deduce or approximate meaning.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Our results are in accordance with those of Horiba et al (1993), who also observed more top-down processing in L2 English based on a sample of 17-and 18-year-old students. Their readers used more intrusions in L2, thus showing top-down elaborative processing that L2 readers use to deduce or approximate meaning.…”
Section: Discussionsupporting
confidence: 95%
“…Bilinguals may be more inclined to bottom-up processing than monolinguals, who may tend to utilise top-down processing. Horiba et al (1993) investigated intrusions that indicate the influence of schemata, scripts activated or gist formed during the comprehension stage on the reconstruction of the story in free recall; however, their argument is based on bilinguals' L2 usage. They contended that because bilinguals constantly deal with two language systems, they have to develop a focus on the linguistic surface structure of their verbal input.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The examination of L2 reading studies that employed the recall assessment task revealed that research has varied in terms of the time allowed for doing the recall task. As seen in Table 1, while some researchers allowed the participants to read and recall at their own pace (e.g., Allen et al, 1988;Barry & Lazarte, 1995;Barry & Lazarte, 1998;Bernhardt, 1983;Chen & Donin, 1997;Connor, 1984;Donin & Silva, 1993;Horiba, 1996a, b;Horiba et al, 1993;Riley & Lee, 1996;Sadoski et al, 2000;Schraw, 1998;Stott, 2004;Young, 1999), others set a certain time limit and asked the participants to finish the task within the time limit (e.g., Baylor & McCormick, 2003;Chu et al, 2002;Davis et al, 1988;Ghaith & Harkouss, 2003;Kim, 1995;Sadoski et al, 1995).…”
Section: Literature Reviewmentioning
confidence: 98%